Application of networked water balance model in refined management of steel industrial park. Issue 3 (23rd December 2021) - Wang, Yurong; Li, Linyuan; He, Wentao; Zhang, Xinli; Li, Xuanjin; Li, Xiang; Li, Hongying
Abstract: Water shortages have become a major constraint on China's industrial development. Iron and steel industrial parks have a huge demand for water resources and complex production technologies. Therefore, it is very important to study the distribution, transfer and loss of water resources in industrial parks in order to improve the ability to refine water resources management. The purpose of this study was to reveal the water flow in industrial parks by using the principle of water balance and to provide a method for quantification and characteristic recognition of water resources in industrial production processes. In this research, an iron and steel industrial park in North China was chosen as the case study. In order to calculate the water balance of the whole steel production processes, the industrial park was divided into four levels and 110 water units according to the pipe network system and production processes. Based on the results of multi-level and multi-node water balance, this paper analyzed the water intake structure and water consumption structure of industrial parks, and provided the methods to optimize the allocation of water resources and reduce the consumption of fresh water in industrial production processes. The results of the study showed that the energy department accounted for 60.8% of the total water withdrawal of the industrial park. There were 6, 249 m 3 /day of fresh water in the industrial park, which could be replaced by reclaimed water from urban sewage. Evaporation and pipe network leakage were the main water consumption factors in the steel park, which contributed 91.3% of the water consumption. Under the guidance of the research results, the evaporation water consumption of the industrial park was reduced by 8, 412 m 3 /day, and pipe leakage was reduced by 600 m 3 /day. This article demonstrates the application of the water balance principle in complex water use systems, which is helpful for water resources management based on water use processes. HIGHLIGHTS: A water balance network model based on the industrial production process is proposed. The model quantifies the transfer and loss of water resources during steel production, making the previously neglected water visible. The water intake structure evaluates the amount of fresh water that can be replaced by unconventional water resources in the industrial park and establishes the flow relationship between urban sewage and industrial water. Water consumption structure found the main water consumption factors, location and quantity of the industrial park. The problem of unclear characteristics of industrial water consumption has been solved.